2023
DOI: 10.1186/s12987-023-00431-6
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system insulin signaling can influence the rate of insulin influx into brain

Abstract: Background Insulin transport across the blood-brain barrier (BBB) is a highly regulated, saturable process, known to be affected by many peripheral substrates including insulin itself and triglycerides. This is in contrast to insulin leakage into peripheral tissues. Whether the central nervous system (CNS) can control the rate of insulin uptake by brain remains to be determined. Insulin BBB interactions are impaired in Alzheimer’s disease (AD) and CNS insulin resistance is widely prevalent in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It is also very likely that what we observe in the hippocampus does not reflect what is going on in other insulin‐rich brain regions. Although insulin is present throughout the brain, there are significant differences in insulin levels between different brain regions, particularly the olfactory bulb and hypothalamus (which are characterized by the highest insulin levels), and the amygdala and midbrain, which contain much less insulin 75,80 . Regional specificities in the response to DR are worthy of further investigation, particularly in the context of the possible specific role that insulin plays in these regions, but unfortunately, this type of analysis significantly exceeds the experimental design presented in this article.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is also very likely that what we observe in the hippocampus does not reflect what is going on in other insulin‐rich brain regions. Although insulin is present throughout the brain, there are significant differences in insulin levels between different brain regions, particularly the olfactory bulb and hypothalamus (which are characterized by the highest insulin levels), and the amygdala and midbrain, which contain much less insulin 75,80 . Regional specificities in the response to DR are worthy of further investigation, particularly in the context of the possible specific role that insulin plays in these regions, but unfortunately, this type of analysis significantly exceeds the experimental design presented in this article.…”
Section: Discussionmentioning
confidence: 90%
“…Accordingly, it has been shown that an increase in serum insulin under normal, physiological conditions may cause only a small increase in the insulin in the cerebrospinal and interstitial fluids 74 . However, insulin transport across the blood–brain barrier could be affected by other serum parameters like triglycerides, 75 while the ratio of serum to brain and CSF insulin could be changed due to various factors, including the age of the subject 72–74 or in certain pathologic conditions such as inflammation, when markedly increased insulin transport to the brain has been noted 76 . Interestingly, a high‐fat diet is associated with a significantly decreased insulin transport rate to the brain, 77 while the deregulation of insulin transport to the brain caused by obesity could be restored by caloric restriction 78 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 and we have shown loss of brain IR signaling slows insulin transport into the brain in mice. 50 Therefore, it is possible the dysregulated processing of the sIR by insulin could perpetuate a vicious cycle, leading ultimately to brain insulin resistance and deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is essential for glutamatergic signaling, BBB integrity, vasodilation, neuronal proliferation, differentiation, cognition, and memory ( Åberg et al, 2003 ; Hallschmid et al, 2007 ; Sawallisch et al, 2009 ; Heni et al, 2011 ; Irvine et al, 2011 ; Kuwabara et al, 2011 ; Chirivella et al, 2017 ; Pomytkin et al, 2019 ; Fetterly et al, 2021 ; Wang et al, 2022 ; Nguyen et al, 2023 ). Changes to insulin signaling, particularly desensitization to insulin, result in chronic inflammation and are a known risk factor for AD across human and rodent in vitro and in vivo models ( Baker et al, 2011 ; Blázquez et al, 2014 ; Craft et al, 2017 ).…”
Section: Other Regulatory Rnasmentioning
confidence: 99%